GC–MS Phytochemical Characterization and Comparative Antidiabetic Activities of Methanolic Extracts of Calotropis gigantea Leaves, Stem Bark, and Roots in Streptozotocin-Induced Diabetic Rats - Mercy iliya Tumba; Isaac John Umaru; Chinedu Imo (Darul Yasin Al Sys, 2026)
Calotropis gigantea is widely used in traditional medicine for treating various health conditions. This study evaluated the phytochemical composition and comparative therapeutic effects of methanolic extracts from its leaves, stem bark, and roots in streptozotocin (STZ)-induced diabetic albino rats. Plant materials were air-dried, pulverized, and extracted through cold maceration in methanol for 72 hours, after which the extracts were concentrated using a rotary evaporator and characterized by gas chromatography–mass spectrometry (GC–MS). Thirty-six male albino rats were randomly assigned to six groups: normal control, diabetic control, metformin-treated (100 mg/kg), and leaf-, stem-bark-, and root-extract-treated groups (100 mg/kg each). Treatments were administered for 14 days. Fasting blood glucose, liver and kidney function indices, and lipid profiles were assessed, alongside histopathological examination of liver and kidney tissues. GC–MS identified several bioactive compounds, including the oxygenated monoterpenes 7-octen-2-ol, α-terpineol, and D-limonene, indicating potential antioxidant relevance. Diabetes induction increased fasting blood glucose from 4.93 ± 0.25 to 16.14 ± 0.98 mmol/L, and concentrations remained elevated in untreated diabetic rats. All extracts significantly reduced blood glucose, with the root extract producing the greatest reduction, from 15.37 ± 1.10 to 8.93 ± 1.94 mmol/L, comparable to the response observed with metformin. The root and leaf extracts demonstrated the strongest improvements in renal function indices, whereas the leaf extract produced the most pronounced reductions in alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase activities. The leaf extract also reduced serum triglyceride and cholesterol concentrations while increasing high-density lipoprotein levels. Histopathological findings corroborated the biochemical results by demonstrating reduced liver and kidney tissue damage in treated animals. These findings indicate that C. gigantea, particularly its root and leaf extracts, possesses antidiabetic, hepatoprotective, nephroprotective, and lipid-modulating potential, supporting its further investigation as a candidate for managing diabetes mellitus and its associated complications.